Militarizing Sri Lanka : popular culture, memory and narrative in the armed conflict - De Mel, Neloufer (Sage Publications, 2007)
Militarizing Sri Lanka is a study of the militarization that has buttressed. the war between the Sri Lankan state and the LTTE for over two decades. It highlights. militarization as a process through which the ideology of militarism is shaped. and shared in a manner that makes militant solutions to conflict a part of institutional. structures and ways of thought. It foregrounds militarization as activity and. agency, capable of adaptation and transforming society in significant ways; and. as a deeply gendered, contingent and shifting process. It also analyzes both the. construction and resista.